Gastroretentive floating matrix tablets of cephradine based on psyllium husk. Issue 3 (2nd May 2019) - Sher, Muhammad; Basharat, Bushra; Hassan, Faiza; Naeem-ul-Hassan, Muhammad; Bukhari, Syed Nasir Abbas; Hussain, Muhammad Ajaz
Abstract : Sustained-release gastroretentive floating matrix tablets of cephradine were prepared for better patient compliance. Eight different tablets were prepared by using two natural polymers, psyllium husk powder (F1–F4) and xanthan gum (F5–F8), through the wet granulation technique. These tablets were characterized by pre- and postcompression analysis, Fourier transform infrared spectroscopy, swelling index study, in vitro buoyancy and dissolution study. Data were analyzed by model-dependent and model-independent analysis to devise the release mechanisms. The polymers exhibited excellent sustained-release behavior as well as binding characteristics. Pre- and postcompression parameters were observed in the specified official pharmacopoeia range. The drug contents of all the formulations were found in the range 95·52–99·63%. No chemical interaction was found between the drug and polymer. All formulations exhibited a good floating time – that is, >24 h – except F8, which remained buoyant for less than 1 h in simulated gastric fluid (pH 1·2). All of the formulations exhibited a direct relation between the swelling index and viscosity of polymer matrices. The significance of the wet granulation technique was indicated by the polymer action as a binding agent in wetting solution. From comparison of the two polymers, psyllium husk powder efficiently retarded the drug release owing to its high gelatinous swollen mass.